SYAIKH MOHAMED IDRIS AL-MARBAWI: Kontribusinya dalam Fiqh al-Hadîs - Faisal bin Ahmad Shah (State Islamic University North Sumatra, 2010)
Abstrak: Sheikh Mohamed Idris al-Marbawi: His Contribution in Fiqh al-Hadîth. Syaikh Mohamed Idris bin Abdul Raof al-Marbawi’s Bahr al-Madhi is a very popular work within the Malaysian community. This work comprizes a translation of 2781 prophetic traditions adapted from Imâm al-Tirmidhî’s al-Jâmi‘, and still continuously reprented and used by large audience in mosques. This study focuses on studying the method of exegesis (syarh) of fiqh al-hadîs found in Bahr al-Madhi. As such, the writer analyzes document and makes interviews related to issues relevant to the study. The test for methods used by al-Marbawy in Fiqh al-hadîs is conducted by analyzing the findings through varius interpretaion of al-Hadis. In addition, comparative approach is also used by referring to the works of expert in hadith and identifying how far al-Marbawi’s method is similar or diferent to the former views. This study reveals that al-Marbawi’s commentary on Fiqh al- Hadîs is mainly dominated by issues pertaining to ‘aqîdah (Islamic creed), tafsîr (Qur’anic exegesis), hadîs (Islamic traditions), usûl al-fiqh (Islamic jurisprudence), and history and language. Finally, the writer asserts that due to its divergence scope of discussion, authentivcity andreliability, the Bahr al-Madhi remains the main reference in hadith studies applicable for different disciplines of knowledge. Kata Kunci: Mohamed Idris al-Marbawi, Fiqh al-hadis, Bahr al-Madhi